Enhancing Public Service Quality: The Role of Professionalism, Service Delivery, and Mediating Effects of Service Quality on Customer Satisfaction in Government Institutions - Muhammad Naufal Rajif (Jurnal Sistem Informasi Bisnis, 2026)
This study examines the impact of professionalism and service delivery on service quality and customer satisfaction in public administration, with a focus on the Bukittinggi City Samsat Office. The research also explores the mediating role of service quality in these relationships. The study employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze survey data collected from 100 respondents. The SERVQUAL model serves as the theoretical foundation, with professionalism and service delivery as key predictors of service quality and customer satisfaction. The results indicate that professionalism significantly influences service quality and customer satisfaction. Similarly, service delivery has a strong positive effect on both service quality and customer satisfaction. Moreover, service quality acts as a significant mediator, reinforcing the need for continuous improvements in employee professionalism, structured service processes, and customer engagement. These findings highlight the importance of service quality as a central factor in public service management. Government agencies should focus on digital transformation, workflow optimization, and employee training to improve service delivery. The study also suggests integrating Business Information Systems (BIS) to enhance data-driven decision-making and service performance monitoring. This study contributes to the public service quality literature by examining the interplay between professionalism, service delivery, and customer satisfaction using SEM-PLS. It provides practical recommendations for improving e-Government services and enhancing public trust in government institutions.